A Semiotiotic Approach to Poetic Intention and the Challenges Involved - Mohammad Mohammad khaqani Esfahani; Reza Amer (دراسات فی اللغه العربیه و آدابها)
Semiotics has experienced many developments in the final decades of the twentieth century , espeually in connection with the intended meaning in contemporary poetry . This has led to several schemes in the scholarly study of literary texts either in formal aspects or in its content and purposes . Of Course , the intended meaning present in the deep structures should never be distorted or sacrificed in the course of any kind of interpretive procedure . Therefore , the critical study of intention in the contemporary poetry is one of the important issues in literary criticism which modern scholars have dealt with in their interpretation of signs in literary texts using semiotic approaches without destroying the Arabic identity of poems . The suggested opproach to interpretation dose not reduce literary criticism to more reference to science and fidds of knowledge nor confines it to any particular frame of reference but opens up the text to different domains of knowledge dding to its tolerance of various views and understandings . New text analytical approaches are critical procedureswhich allow for different outlooks in the examination of modern Arabic texts both at theoretical and applied levels . This article intends to emphasize the significance of the semiotic method in the study of modern Arabic texts and exposes the most important challenges in modern poetry , especially in connection with the differences among the critics about the literary productions . It also tries to explain the methods of analysis both at the formal level and content level for reaching sound interpretation .